Correction: Atomic-scale investigation of cation doping and defect clustering in the anti-perovskite Na3OCl sodium-ion conductor. Issue 22 (20th May 2022) - Goldmann, Benedek A.; Clarke, Matt J.; Dawson, James A.; Islam, M. Saiful
Abstract : Correction for 'Atomic-scale investigation of cation doping and defect clustering in the anti-perovskite Na3 OCl sodium-ion conductor' by Benedek A. Goldmann et al., J. Mater. Chem. A, 2022, 10, 2249–2255, ; https://doi.org/10.1039/D1TA07588H .